We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
128
1
avatar

Hi everyone, any help appreciated!

 Oct 4, 2018

Best Answer 

 #1
avatar+18118 
+2

Multiply the second term by   sqrt(n - 1)  /  Sqrt(n-1)

 

 

then you would have    { 1  +  (n-1)  }  / sqrt(n-1) ===   n / sqrt(n-1)    

 Oct 4, 2018
 #1
avatar+18118 
+2
Best Answer

Multiply the second term by   sqrt(n - 1)  /  Sqrt(n-1)

 

 

then you would have    { 1  +  (n-1)  }  / sqrt(n-1) ===   n / sqrt(n-1)    

ElectricPavlov Oct 4, 2018

26 Online Users

avatar
avatar